Amazonian Castilian in the Novel Paiche. Dialectological Analysis - Pau, Stefano (2020)
Taking as a starting point the peculiarities that characterize the Peruvian Amazonian Spanish in its different varieties, this paper proposes a dialectological analysis of the novel Paiche by the writer and painter César Calvo de Araújo. Firstly, we examine the strategies used by the author to condense and reproduce the main items of the phonological system on the written page, and secondly, we analyze the morpho-syntactic dimension, paying special attention to the aspects related to the possessive and the nominal disagreement.